UPAYA AMERIKA SERIKAT DALAM MENANGGULANGI ANCAMAN HIV DAN AIDS DI NEGARA-NEGARA AFRIKA MELALUI PRESIDENT’S EMERGENCY PLAN FOR AIDS RELIEF - Damajanti, Fathnisa Tya; Utomo, Tri Cahyo (Journal of International Relations, 2018)
The United States is a country that takes HIV and AIDS cases seriously. They has seen HIV and AIDS as a threat and to overcome this threat, they launched a program called PEPFAR. PEPFAR is a program that has a goal to overcome the problem of HIV and AIDS, especially, in developing countries. Of the many continents in the world, the African region is an area that, it can be said, is highly preferred by PEPFAR to seek HIV and AIDS prevention in the region. Because, the number of HIV and AIDS cases in this region is very high. This research aims to describe the threat of HIV and AIDS in the African region. Using qualitative methods and analysis with the human security approach, it is known that the efforts of the United States to overcome cases of HIV and AIDS in the African region through PEPFAR are driven by the United States' concern for the threat of health security in the African region.